Academic writing and grammar for students - Osmond, Alex. (Los Angeles ; Thousand Oaks, Calif. : SAGE, 2013)
This guide shows students how to use academic English grammar and punctuation. The author identifies common grammar mistakes and how to avoid them, making extensive use of examples and advice from tutors from a range of subjects.
Introduction: the aims of this book and how to use it -- Basic conventions of academic writing -- Basic grammatical concepts -- Putting sentences together -- Putting paragraphs together -- Critical thinking and referencing -- Conciseness and clarity -- Common mistakes and how to deal with them -- Proofreading effectively.
Keywords: Academic writing -- Handbooks, manuals, etc; Dissertations, Academic -- Authorship -- Handbooks, manuals, etc; Academic writing; Dissertations, Academic -- Authorship; Handbooks and manuals